2022
DOI: 10.1016/j.bioactmat.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterns and peptide gradient on the inner surface of a guidance conduit synergistically promotes nerve regeneration in vivo

Abstract: Both of the surface topographical features and distribution of biochemical cues can influence the cell-substrate interactions and thereby tissue regeneration in vivo . However, they have not been combined simultaneously onto a biodegradable scaffold to demonstrate the synergistic role so far. In this study, a proof-of-concept study is performed to prepare micropatterns and peptide gradient on the inner wall of a poly (D,L-lactide- co -caprolactone) (PLCL) guidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…It could be shown that the 3D-printed collagen lines led to a better axonal regeneration and remyelination than bulk collagen hydrogel filling, indicating that spatially controlled patterning of substrates that promote cell attachment can be a promising strategy that combines structural and substrate-mediated cues ( Yoo et al, 2020 ). Similarly, in a very recent study a grooved PLCL conduit in combination with a patterned gradient of a laminin-derived peptide showed synergistic effects on aligned migration of SCs in vitro and significantly accelerated nerve recovery in vivo ( Zhang et al, 2021 ).…”
Section: Biological Functionalization Beyond the Hollow Tubementioning
confidence: 88%
“…It could be shown that the 3D-printed collagen lines led to a better axonal regeneration and remyelination than bulk collagen hydrogel filling, indicating that spatially controlled patterning of substrates that promote cell attachment can be a promising strategy that combines structural and substrate-mediated cues ( Yoo et al, 2020 ). Similarly, in a very recent study a grooved PLCL conduit in combination with a patterned gradient of a laminin-derived peptide showed synergistic effects on aligned migration of SCs in vitro and significantly accelerated nerve recovery in vivo ( Zhang et al, 2021 ).…”
Section: Biological Functionalization Beyond the Hollow Tubementioning
confidence: 88%
“…Recent findings showed the involvement of macrophages and their polarization to M2 phenotype enabled the migration, proliferation and remyelination of SCs, which subsequently facilitated axonal extension for better restoration of sciatic nerve function. During this process, the physical architecture impairment of nerve bundle trigger monocytes infiltration and transfer to macrophages; thereafter, macrophage tends to polarize to M2 phenotype on integral oriented basal matrix, while M1 phenotype on irregular basal matrix 19 , 20 , 93 , consolidating the fact that support structure and biomechanical properties guide cell behaviors of macrophage. Accumulating evidence indicated mechanical modulation-induced YAP/TAZ activation may lead to M2 polarization of macrophages 94 , but more details need to clarify.…”
Section: Biomechanics-based Pathophysiological Responses and Regenera...mentioning
confidence: 99%
“…As mentioned above, composited nerve grafts as regenerative platforms during PNR aim to display agreeable stiffness for refined mechanical signal activation 78 , 145 . A wide range of specialized physical architectures of nerve grafts including net-like filament, porous structure and aligned micro-/nano-topography also contribute to the improvement of mechanical properties, affecting repair outcomes of neural fiber 22 , 93 , 146 , 147 .…”
Section: Biomechanics-based Tissue Engineering Strategies For Pni Man...mentioning
confidence: 99%
“…28,29 Specifically, the microgrooved surface structure has been reported to facilitate the cell growth and development of SCs and achieve aligned axon growth, which reduces the wrong target reinnervation. 30,31 Athough RGD peprtides as biological signals or anisotropic topography as a key physical factor to provide guidence cues has been explored for directing axon regeneration and nerve repair indepently, the desirable repair of large-gap peripheral nerve injuries with functional recovery still remains a great challenge. Therefore, it is necessary to develop bioengineered NGCs with therapeutic multicues to achieve improved peripheral nerve regeneration.…”
mentioning
confidence: 99%
“…Based on superior spatial and temporal precision of light, the phototriggered gelation system has been regarded as a powerful tool for introducing biochemical signals to scaffolds in a noninvasive and highly controllable manner for directing cell fate. Significantly, due to the high efficiency of rapid photochemistry upon simple irradiation, photo-cross-linking reactions provide a multifunctional strategy not only to incorporate biomolecules but also to spatially create robust physical microenvironments within biomaterials, such as surface topographic structure and stiffening and softening regions. , Currently, introducing anisotropic topography, a key physical factor of biomedical materials has shown success in promoting axon regeneration. , Specifically, the microgrooved surface structure has been reported to facilitate the cell growth and development of SCs and achieve aligned axon growth, which reduces the wrong target reinnervation. , …”
mentioning
confidence: 99%